CO/CO2 ratio in biomass char oxidation. (August 2017) - Anca-Couce, Andrés; Sommersacher, Peter; Shiehnejadhesar, Ali; Mehrabian, Ramin; Hochenauer, Christoph; Scharler, Robert
Abstract: The CO/CO2 release ratio obtained during char combustion of single biomass particles has been analysed in this work experimentally and by modelling. Experiments have been conducted with spruce, straw and Miscanthus pellets at different temperatures. Furthermore, these experiments have been modelled with a single particle model coupled with a CFD model of the single particle reactor. The results show that the CO/CO2 ratio strongly depends on the feedstock, being lower for spruce than for straw or Miscanthus. Furthermore, the most commonly employed correlations for this ratio in literature are not adequate, as they either under- or over-predict it.